Penerapan Arsitektur Salutogenik pada Bangunan Community Hub Lansia di Pekanbaru - Wahyuni, Febri; Imbardi, Imbardi; Atika, Mutiara Yaumil (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
Increasing age in the elderly is often accompanied by various multidimensional challenges that include physical, psychological and social aspects, thus having the potential to significantly reduce their quality of life. In line with increasing life expectancy and the increasing elderly population, modern life which increasingly emphasizes independence and individualism triggers social trends that can worsen the conditions of the elderly, such as increasing the risk of social isolation, alienation and reducing their role and involvement in the community. This phenomenon demands an environmental design strategy that not only provides elderly-friendly facilities, but is also able to accommodate the needs of the elderly holistically. The Elderly Community Hub concept with a Salutogenic Architecture approach was developed as a response to this challenge, with the aim of creating an environment that actively supports the physical, mental and social health of elderly people through design oriented towards improving the quality of life. This design is designed to integrate elements of health, social interaction and recreational activities in a sustainable manner, so as to be able to build an inclusive ecosystem that empowers the elderly in social life.